The Etiology of Observed Negative Emotionality from 14 to 24 Months - Rhee, Soo H.; Corley, Robin P.; Friedman, Naomi P.; Hewitt, John K.; Hink, Laura K.; Johnson, Daniel P.; Robinson, JoAnn; Smith, Ashley K.; Young, Susan E. (Frontiers in Genetics, 2012)
We examined the magnitude of genetic and environmental influences on observed negative emotionality at age 14, 20, and 24 months. Participants were 403 same-sex twin pairs recruited from the Longitudinal Twin Study whose emotional responses to four different situations were coded by independent raters. Negative emotionality showed significant consistency across settings, and there was evidence of a latent underlying negative emotionality construct. Heritability decreased, and the magnitude of shared environmental influences increased, for the latent negative emotionality construct from age 14 to 24 months. There were significant correlations between negative emotionality assessed at age 14, 20, and 24 months, and results suggested common genetic and shared environmental influences affecting negative emotionality across age, and that age-specific influences are limited to nonshared environmental influences, which include measurement error.